1999
DOI: 10.1002/1531-8257(199901)14:1<10::aid-mds1005>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach to the study of heterogeneity in idiopathic Parkinson's disease: identification of three distinct subtypes

Abstract: Idiopathic Parkinson's disease (IPD) has been subclassified on the basis of predominant motor symptomatology, age at disease onset, depressive affect, and cognitive performance. However, subgroups are usually arbitrarily defined and not reliably based on qualitatively distinct neuropathology. We explored heterogeneity in IPD in a data‐driven manner using comprehensive demographic, motor, mood, and cognitive information collected from 176 patients with IPD. Cluster analysis revealed three subgroups of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 65 publications
1
104
3
Order By: Relevance
“…Groups of patients are collected based on whether they share a particular feature, and then the subgrouping is evaluated by making further comparisons with respect to other features of the disease. This method has been criticized as being too arbitrary in the choice of initial sub-grouping [25] but has yielded much information that can be utilized in future studies. The following section is a systematic review of the basis for sub-classifying IPD, following a literature search of the Medline databases 1966-2000, using exploded MeSH headings,"Parkinson" and "Heterogeneity".…”
Section: Approaches To the Classification Of Ipdmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups of patients are collected based on whether they share a particular feature, and then the subgrouping is evaluated by making further comparisons with respect to other features of the disease. This method has been criticized as being too arbitrary in the choice of initial sub-grouping [25] but has yielded much information that can be utilized in future studies. The following section is a systematic review of the basis for sub-classifying IPD, following a literature search of the Medline databases 1966-2000, using exploded MeSH headings,"Parkinson" and "Heterogeneity".…”
Section: Approaches To the Classification Of Ipdmentioning
confidence: 99%
“…Cluster analysis has been applied to a case series of patients with IPD [25] with the formation of three subgroups of patients, a "motor only", a "motor and cognitive", and a "rapidly progressive" group. Not unexpectedly, these subgroups differed on the basis of the variables that were entered into the original clustering model.…”
Section: S Heterogeneity Based On Pathologymentioning
confidence: 99%
“…31,32 It is possible that these subtypes may represent different phenotypes, eventually leading to the identification of genetically determined factors. The choice of optimal therapeutic approach may, in the future, depend on such a complete characterization of patients.…”
Section: Subtypes Of Pdmentioning
confidence: 99%
“…Several population-and hospital-based studies confirm this clinical heterogeneity [4,13,17,27]. Three studies used cluster analysis as a statistical way to explore the presence of different clinical subgroups.…”
Section: Introductionmentioning
confidence: 98%
“…Three studies used cluster analysis as a statistical way to explore the presence of different clinical subgroups. One study described three different subgroups "motor impaired only", "motor and cognitive impaired", and "rapidly progressive" [13]. Another study identified four ■ Abstract Objective To determine clinical heterogeneity in newly diagnosed Parkinson's disease using cluster analysis and to describe the subgroups in terms of impairment, disability, perceived quality of life, and use of dopaminergic therapy.…”
Section: Introductionmentioning
confidence: 99%